2023
DOI: 10.1002/hyp.15009
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological and meteorological drivers of ephemeral pond hydrology in the Canadian shield forest

Marjolaine Roux,
Marie Larocque,
Philippe Nolet
et al.

Abstract: Ephemeral ponds in cold and humid forested regions are often vulnerable because of their small size and ephemeral nature. The aim of this study was to identify the geomorphological and meteorological drivers of ephemeral pond hydrology in the forests of cold and humid climates. A multi‐year study of 40 ponds was conducted in the Kenauk forest located in the Canadian Shield of the Outaouais region (Quebec, Canada). Pond bathymetry, mineral and organic sediment thickness, watershed area, slope, canopy cover and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 42 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…The shape parameter p suggested by Brooks and Hayashi (2002) to represent pond geometry varies between 0.87 (HP17) and 4.7 (HP27) ( p < 1 corresponding to a convex profile, p > 1 corresponding to a concave profile and p = 1 corresponding to straight slopes). Roux et al (2023) also showed that the EPs are located in small bedrock depressions and are underlain by a layer of low permeability material (fine sand, silt, clay or organic material). Their maximum areas vary between 50.2 m 2 (S6) and 1808.8 m 2 (HP26), and their maximum water depths vary between 0.12 m (HP27) and 0.67 m (S6).…”
Section: Study Areamentioning
confidence: 94%
See 4 more Smart Citations
“…The shape parameter p suggested by Brooks and Hayashi (2002) to represent pond geometry varies between 0.87 (HP17) and 4.7 (HP27) ( p < 1 corresponding to a convex profile, p > 1 corresponding to a concave profile and p = 1 corresponding to straight slopes). Roux et al (2023) also showed that the EPs are located in small bedrock depressions and are underlain by a layer of low permeability material (fine sand, silt, clay or organic material). Their maximum areas vary between 50.2 m 2 (S6) and 1808.8 m 2 (HP26), and their maximum water depths vary between 0.12 m (HP27) and 0.67 m (S6).…”
Section: Study Areamentioning
confidence: 94%
“…Potholes represent small depressional areas at the HRU scale and are isolated wetlands with no flows exchanged with the main channel unless maximum storage is exceeded. Differences between the two algorithms are in the spatial representation, in the T A B L E 1 Morphology and geology of the 10 studied ephemeral ponds, including maximum volume, maximum area, maximum depth, underlying sediment type, sediment thickness, watershed area, spring hydroperiod (SHP) and hydroperiod index (HPi) (data from Roux et al, 2023). The values in brackets are the maximum and minimum observed values over the monitoring period.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations